74‐2: Sunlight‐Readable Low‐Reflection FFS‐LCD. Issue 1 (30th May 2018) - Kawahira, Yuichi; Murata, Koji; Nakai, Takako; Hasegawa, Masahiro; Sakai, Akira; Minoura, Kiyoshi; Nakatani, Aya; Miyata, Hidekazu; Kyoukane, Youzou; Watanabe, Hisashi; Smith, Nathan
Abstract : A novel wide‐view LCD with reduced unwanted reflection has been developed to enhance ambient contrast ratio. By combining an FFS‐based new LC mode with a circular polarizer, our 12.3" prototype has successfully demonstrated excellent sunlight‐readability without boosting the backlight brightness.